Studies of the Association of Dyes with Surfactants in Aqueous Solutions: Spectrophotometry and Computer Simulation - Shapovalov, Serghey; Ponomariov, Vadim; Mosharenkova, Oryna; Butenko, Sophia (Київський національний університет імені Тараса Шевченка, 2019)
The association of cationic dye (pinacyanol, PC) with anionic dyes (ethyleosin, EE, or rhodamine 200 C, R200C), and also the interaction “dye+surfactant” has been investigated in aqueous solutions by visible spectroscopy and computer simulation. Cetylpyridinium bromide (CPB), sodium dodecylsulfate (SDS) and triton X-100 (TX) were used as cationic, anionic and non-ionic surfactants respectively. The formation of “dye+surfactant” associates takes place at low dye concentrations (≥10‑6 M) and concentrations of surfactant, which are much smaller than the critical micelle concentrations (CMC). In contrast, similar concentrations (10‑6 – 10‑4 M) of small cations of tetramethylammonium or tetraethylammonium have no noticeable effect on the absorption spectra of the dye in the “dye+tetraalkylammonium salt” systems; it indicates the absence of formation of new compound between the dye and salt. The standard enthalpy of formation of “dye+dye” or “dye+surfactant” associates has been determined by AM1 and PM3 semiempirical methods. The computer simulation confirms that the formation of these associates is energetically beneficial.
Keywords: association; aqueous solutions; dyes; enthalpy of formation; spectroscopy; surfactants; semiempirical methods